ANALYSIS OF THE DEVELOPMENT OF CHILDREN'S PEDAGOGY IN THE INTEGRATION OF DEEP LEARNING AND CODING IN ISLAMIC RELIGIOUS EDUCATION LEARNING IN ELEMENTARY SCHOOLS - Rozana, Salma; Evi Dayanti; Sahrijal Akino; Sondang Siregar (An-Nahdlah: Jurnal Pendidikan Islam, 2026)
This study aims to develop and examine the effectiveness of the Islamic Techno-pedagogy model through the integration of deep learning and coding in Islamic Religious Education (PAI) at the elementary school level. A Research and Development (R&D) approach using Design-Based Research (DBR) was combined with a Pretest–Posttest Control Group Quasi-Experimental Design. The findings revealed that in the first cycle, students’ active participation reached 42% and their Islamic conceptual understanding scored 62/100. After revising the model by adding a spiritual reflection component, participation increased to 85% and conceptual understanding reached 88 by the third cycle. The Independent Sample T-Test results showed a significant difference (p < 0.01) between the experimental and control groups, with an average N-Gain Score of 0.75 (high category). The Islamic Techno-pedagogy model effectively integrates digital rationality with Islamic spiritual values, simultaneously enhancing students’ cognitive, affective, and psychomotor domains. Thus, the integration of deep learning and coding in Islamic Religious Education not only strengthens critical and digital thinking skills but also serves as a contemplative medium for shaping students’ religious consciousness in the digital age.